2014
DOI: 10.1242/dev.102699
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic epidermis contains a diverse Langerhans cell precursor pool

Abstract: Despite intense efforts, the exact phenotype of the epidermal Langerhans cell (LC) precursors during human ontogeny has not been determined yet. These elusive precursors are believed to migrate into the embryonic skin and to express primitive surface markers, including CD36, but not typical LC markers such as CD1a, CD1c and CD207. The aim of this study was to further characterize the phenotype of LC precursors in human embryonic epidermis and to compare it with that of LCs in healthy adult skin. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
2
16
0
1
Order By: Relevance
“…The sequential formation of human fetal LC from myeloid precursors has been observed in detailed microscopic studies and ascribed to non-monocyte precursors. 166 In the steady state, the influence of TGF-b, E-cadherin/ b-catenin and the binding of Axl to gas 6 maintains LC in a quiescent state. 151,152,167,168 In postnatal life, local self-renewal restores LC numbers following chronic or low-grade inflammatory insults.…”
Section: Developmentmentioning
confidence: 99%
“…The sequential formation of human fetal LC from myeloid precursors has been observed in detailed microscopic studies and ascribed to non-monocyte precursors. 166 In the steady state, the influence of TGF-b, E-cadherin/ b-catenin and the binding of Axl to gas 6 maintains LC in a quiescent state. 151,152,167,168 In postnatal life, local self-renewal restores LC numbers following chronic or low-grade inflammatory insults.…”
Section: Developmentmentioning
confidence: 99%
“…In the 8 th GW, melanocytes start migrating from the neuroectoderm, the neural crest, into the skin. Merkel cells and Langerhans cells are detectable in the epidermis from the 10 th -15 th GW onwards [19]. Subcutaneous adipose tissue starts forming in the 18 th GW (Figure 2d).…”
Section: Adnexal Structures and Other Components Of Fetal Skinmentioning
confidence: 98%
“…Although equivalent studies cannot be carried out in humans, several reports suggest that human LCs share similar properties. In humans, the infiltration of embryonic dermis with LC precursors can be observed at early time points . Proliferating LCs were identified in human skin, and graft‐resident LCs were also found to remain for several years in a transplanted human limb graft .…”
Section: The Lch Cell Of Originmentioning
confidence: 99%
“…In humans, the infiltration of embryonic dermis with LC precursors can be observed at early time points. 18 Proliferating LCs were identified in human skin, 19,20 and graft-resident LCs were also found to remain for several years in a transplanted human limb graft. 21 In addition, studies of hematopoietic stem cell recipients showed that LCs become donor-derived when there is inflammation due to graft versus host disease.…”
Section: The Lch Cell Of Originmentioning
confidence: 99%